(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
This research paper explores innovative teaching methodologies that enhance English language education in modern secondary schools. The study discusses the integration of digital learning tools, communicative approaches, task-based learning, and blended learning environments. It highlights how these methods foster creativity, critical thinking, and intercultural communication among students. The findings indicate that adopting modern pedagogical innovations significantly improves students’ motivation and learning outcomes in English education.